Digital microfluidics-engaged automated enzymatic degradation and synthesis of oligosaccharides - Sun, Yunze; Wu, Yiran; Ma, Dachuan; Li, Jian-Jun; Liu, Xianming; You, Yuanjiang; Lu, Jun; Liu, Zhen; Cheng, Xin; Du, Yuguang (Frontiers in Bioengineering and Biotechnology, 2023)
Glycans are an important group of natural biopolymers, which not only play the role of a major biological energy resource but also as signaling molecules. As a result, structural characterization or sequencing of glycans, as well as targeted synthesis of glycans, is of great interest for understanding their structure–function relationship. However, this generally involves tedious manual operations and high reagent consumptions, which are the main technical bottlenecks retarding the advances of both automatic glycan sequencing and synthesis. Until now, automated enzymatic glycan sequencers or synthesizers are still not available on the market. In this study, to promote the development of automation in glycan sequencing or synthesis, first, programmed degradation and synthesis of glycans catalyzed by enzymes were successfully conducted on a digital microfluidic (DMF) device by using microdroplets as microreactors. In order to develop automatic glycan synthesizers and sequencers, a strategy integrating enzymatic oligosaccharide degradation or synthesis and magnetic manipulation to realize the separation and purification process after enzymatic reactions was designed and performed on DMF. An automatic process for enzymatic degradation of tetra-N-acetyl chitotetraose was achieved. Furthermore, the two-step enzymatic synthesis of lacto-N-tetraose was successfully and efficiently completed on the DMF platform. This work demonstrated here would open the door to further develop automatic enzymatic glycan synthesizers or sequencers based on DMF.